MICROFOUNDATIONS OF BRAGAINING IN AGENCY CONTRACTS - Morteza Aalabaf Sabaghi (فصلنامه پژوهش‌های اقتصادی ایران, 2000)
Bargaining in labour markets is a prevalent process for wages negotiations and employment in which there is a particular aspect clearly apparent in agency negotiations. There is a one-to-one aspect of bargaining between firms and workers that develops into contract negotiation in labour markets. This process and the resulting wage contract, is developed further in this paper in a non-cooperative bargaining model.